Thermophiles and Thermozymes - González-Siso, María-Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Interest in the study of life in hot environments, both with respect to the inhabiting microorganisms and the enzymes they produce, is currently very high. The biological mechanisms responsible for the resistance to high temperatures are not yet fully understood, whereas thermostability is a highly required feature for industrial applications. In this e-book, the invited authors provide diverse evidence contributing to the understanding of such mechanisms and the unlocking of the biotechnological potential of thermophiles and thermozymes.